The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fnins.2020.582046
|View full text |Cite
|
Sign up to set email alerts
|

The Dresden Protocol for Multidimensional Walking Assessment (DMWA) in Clinical Practice

Abstract: Walking impairments represent one of the most debilitating symptom areas for people with multiple sclerosis (MS). It is important to detect even slightest walking impairments in order to start and optimize necessary interventions in time to counteract further progression of the disability. For this reason, a regular monitoring through gait analysis is highly necessary. At advanced stages of MS with significant walking impairment, this assessment is also necessary to optimize symptomatic treatment, choose the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 104 publications
0
22
0
2
Order By: Relevance
“…Subjects were tested with GAITRite (CIR-Systems Inc., Franklin, NJ, USA) according to the Dresden Protocol for Multidimensional Gait Assessment (DMWA) [33]. The GAITRite was investigated in numerous studies and has demonstrated high reliability and validity [34][35][36].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects were tested with GAITRite (CIR-Systems Inc., Franklin, NJ, USA) according to the Dresden Protocol for Multidimensional Gait Assessment (DMWA) [33]. The GAITRite was investigated in numerous studies and has demonstrated high reliability and validity [34][35][36].…”
Section: Methodsmentioning
confidence: 99%
“…Selected gait parameters for people with MS and healthy controls (N = 60). Key parameters used in clinical routine according our DMWA protocol[33]; MS = multiple sclerosis; HC = healthy controls; EMIQ = Early Mobility Impairment Questionnaire; MSWS = Multiple Sclerosis Walking Scale; GCT = Gait Cycle Time; L = left; R = right; standard deviation = SD; data in mean ± SD; ( )-dimensionless values; p-value via Mann-Whitney U-Test for differences between groups.…”
mentioning
confidence: 99%
“…In recent years, the Expanded Disease Disability Scale (EDSS) has been an essential, irreplaceable scale in MS which has been improved in the past years by different approaches (127)(128)(129). However, other additional clinical instruments have been introduced to quantitate the different multidimensional aspects of MS as fatigue, cognition or walking function (130,131). The Multiple Sclerosis Functional Composite (MSFC) provides a functional assessment of different key functions (upper and lower extremities, cognition) that is used more and more frequently in MS and has been proven to be highly sensitive in the evaluation of very important clinical trials.…”
Section: Patients Physiological Status Datamentioning
confidence: 99%
“…The Multiple Sclerosis Performance Test (MSPT) is a digital adaptation of the MSFC with additional elements added ( 160 , 161 ) and measures health status via iPad with questionnaire on health status, processing speed with Processing Speed Test (PST) ( 162 ), manual skills with 9-Hole-Peg-Test (9-HPT) and walking speed with Timed 25-Foot-Walk (T25-FW) ( 160 ). Multidimensional gait analysis can be performed with measurement of walking speed (T25-FW), measurement of endurance [2-Minute Walk Test, 2MWT ( 163 , 164 )] and measurement of balance and gait quality on a sensor-based walking mat (GAITRite ® -System, Mobility Lab-System) ( 131 ). For the digital measurement of data in patient-specific everyday life (at home) there are various patient apps such as Floodlight, diverse fitness tracker and health apps available ( 165 , 166 ).…”
Section: Concept Of Digital Twins In the Management Of Multiple Sclerosismentioning
confidence: 99%
See 1 more Smart Citation